A dietary isothiocyanate-enriched moringa (Moringa oleifera) seed extract improves glucose tolerance in a high-fat-diet mouse model and modulates the gut microbiome - Jaja-Chimedza, Asha (J Funct Foods, 2018)
Moringa oleifera (moringa) has been traditionally used for the treatment of diabetes and in water purification. We previously showed that moringa seed extract (MSE), standardized to its primary bioactive isothiocyanate (MIC-1), modulated inflammatory and antioxidant signaling pathways in vitro. To understand the efficacy and mechanisms of action of MSE in vivo, we incorporated MSE into the diets of normal and obese C57Bl/6J male mice fed a standard low-fat diet or a very high-fat diet for 12 wk, respectively. MSE supplementation resulted in reduced body weight, decreased adiposity, improved glucose tolerance, reduced inflammatory gene expression, and increased antioxidant gene expression. 16S rRNA gene sequencing and quantitative PCR of fecal/cecal samples showed major modulation of the gut microbial community and a significantly reduced bacterial load, similar to an antibiotic response. This suggests that MSE improves metabolic health by its intracellular anti-inflammatory and antioxidant activities, and/or its antibiotic-like restructuring of the gut microbiota.